Effects of Online Marketing on Consumer Behaviour: With Reference to Bangalore City: Exploring the Impact of Online Marketing on Consumer Relationships in the Digital Age (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Over the past few years, online media platforms such as Face book, YouTube, Google and Twitter have been growing, allowing consumers to play a more competitive position as business leaders and go (and get there) almost anywhere. This digital media undermine action plans and corporate technology, which have long been developed, but which provide ample growth opportunities by digital, flexible approaches. This article presents a further method of online content effects on consumer relationships and discusses essential modern technology wonders that companies can take into consideration when coping with their associations with consumers in the new media universe.